Konsep Motivasi dan Perannya dalam Pembelajaran - Habsy, Bakhrudin All; Lutfiah, Zahra Rizqi; Sholihuddin, Nasywa Salsabila; Nurarifah, Dinda Yuli; Alfath, Ivan (TSAQOFAH, 2024)
This research aims to analyze the concept of motivation and its role in learning based on a literature review from 10 journals. This research uses a literature study method. The stages of conducting the research started from conducting a literature review from 10 journals regarding the concept of motivation and its role in learning, then analyzing the research starting from the method of collecting library data, reading, taking notes and processing research materials. The results of this research show that motivation can play a role in activating the learning process, maintaining students' interest in the subject matter, increasing students' participation and learning experience, improving students' well-being, and making students feel confident and competent in learning. Therefore, good learning must try to manage student motivation effectively and provide interesting and relevant learning experiences for students. Thus, the concept of motivation and its role in learning has a significant impact on student success and must be carefully considered by teachers and schools.